2016
DOI: 10.7763/ijcea.2016.v7.557
|View full text |Cite
|
Sign up to set email alerts
|

The Liquid-Phase Hydrogenation of Citral to Citronellal at Hydrogen Pressure

Abstract: Abstract-The aim of the work is to obtain citronellal that is the odoriferous substance and refers to the fragrant compounds used in perfumery and in the food industry as a flavoring. It is a raw material for producing aromatic substances -izopulegol, menthol, citronellol et al.The hydrogenation of citral to citronellal was investigated over the catalysts on the base of VIII group metals using special high-pressure kinetic (KEHP) equipment allowing to keep the liquid phase hydrogenation process for any constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…According to the metal, distinct reaction pathways are favored, affording various hydrogenation products . Unsaturated alcohols are generally obtained with gold, ruthenium, or rhodium catalysts through the reduction of the carbonyl group, while palladium catalysts remain highly selective toward the carbon–carbon double bond. , Thus, many heterogeneous palladium catalysts have been applied to the hydrogenation of citral into citronellal with selectivities up to 90%, but they require a good control of the reaction to avoid the formation of dihydrocitronellal and 3,7-dimethyloctan-1-ol at higher conversions. One of the industrial processes is catalyzed by palladium on carbon, in methanol with triethylamine, affording a citronellal yield around 90% .…”
Section: Introductionmentioning
confidence: 99%
“…According to the metal, distinct reaction pathways are favored, affording various hydrogenation products . Unsaturated alcohols are generally obtained with gold, ruthenium, or rhodium catalysts through the reduction of the carbonyl group, while palladium catalysts remain highly selective toward the carbon–carbon double bond. , Thus, many heterogeneous palladium catalysts have been applied to the hydrogenation of citral into citronellal with selectivities up to 90%, but they require a good control of the reaction to avoid the formation of dihydrocitronellal and 3,7-dimethyloctan-1-ol at higher conversions. One of the industrial processes is catalyzed by palladium on carbon, in methanol with triethylamine, affording a citronellal yield around 90% .…”
Section: Introductionmentioning
confidence: 99%
“…6 Unsaturated alcohols are generally obtained with gold, ruthenium or rhodium catalysts through the reduction of the carbonyl group, while palladium catalysts remain highly selective toward the carbon-carbon double bond. [7][8] Thus, many heterogeneous palladium catalysts have been applied to the hydrogenation of citral into citronellal with selectivities up to 90%, [9][10][11][12][13] but require a good control of the reaction to avoid the formation of dihydrocitronellal and 3.7-dimethyloctan-1-ol at higher conversions. One of the industrial processes is catalyzed by a palladium on carbon, in methanol with triethylamine, with a citronellal yield around 90%.…”
Section: Introductionmentioning
confidence: 99%
“…At a reaction temperature of 100 °C and a hydrogen pressure of 0.5 MPa, the citral conversion rate was 100% and citronellal selectivity was 70%. Syunbayev et al 9 studied the activity of group VIII metal (Pd, Ni, Pt, Os, Rh, Ru, Ir-black, and NiR) catalysts in the liquid phase hydrogenation of citral to produce citronellal and the effect of reaction conditions. The results showed that Ru, Ni, and Pd showed high selectivity, which were 93.7, 87.0 and 75.3%, respectively, under the conditions of 2.0 MPa, 30 °C, and 96% ethanol solvent.…”
Section: Introductionmentioning
confidence: 99%